Analisis Indeks Jasa Ekosistem Sebagai Penyedia dan Pengatur Air (Studi Kasus: DAS Kahayan) - Virdy Pyrargyr; Nomeritae Nomeritae; Raden Haryo Saputra (Jurnal Serambi Engineering, 2023)
Ecosystem Services are the benefits that humans obtain from biological natural resource products and ecosystems in the form of direct benefits and direct benefits. This research focuses on ecosystem services as providers and regulators of water in 8 (eight) sub-districts in Central Kalimantan Province and included in the Kahayan River Watershed (DAS). This research aimed is analyze the distribution of the Ecosystem Services Index for water providers and regulators in each sub-district. The Ecosystem Services Index (IJE) in each sub-district is based on 2 parameters, namely land cover and ecoregion/landscape which are scored and weighted against parameters. The largest IJE water provider in the medium category is Rakumpit District (3,584 Ha) and the smallest is Jekan Raya District (2.58 Ha). The largest IJE provider of water in the very low category is Banama Tingang District (29,796 Ha) and the smallest in the very low category is Pahandut District (482 Ha). The largest IJE result as a water regulator in the very high category is Rakumpit District (3,217 Ha) and the smallest is Banama Tingang District (1,407 Ha). The largest water management IJE very low category is Banama Tingang District (25,165 Ha) and the smallest is Sebangau District (296 Ha).